MIDWIVES’ PERCEPTIONS OF THE CONCEPT OF THIRD STAGE OF LABOUR IN DI RS DR TADJUDDIN CHALID MAKASAR - Irdayanti Irdayanti; Dwi Izzati Budiono; Gadis Meinar Sari (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Active management of third stage of labour is an intervention that is considered to reduce the risk of post partum hemorrhage which is the leading cause of maternal mortality. The results of a preliminary study conducted in the labour ward of Dr.Tadjuddin Chalid Makassar hospital it was found that active management was a midwifery care during third stage of labour, besides catheterization and exploration of the uterus routinely carried out in all normal childbirth as part of midwifery care during third stage of labour. This routine interventions can increase the risk of infection and not suitable with the midwives philosophy which states that childbirth is normal physiological processes. Objectives: This study aimed to explore the influence of midwives’ perceptions toward attitudes and behaviour during third stage of labour. Method: A descriptive research study using qualitative methods was conducted in Dr.Tadjuddin Chalid Makassar Hospital. A purposive sample of 5 midwives’ who represent different characteristics participated in this study. Data collection was carried out through in-depth interview and observations. The data analysed according to thematic analysis methods. Findings: The findings included three main themes, 1) Midwives believe that third stage of labour is the most risky phase for all women during childbirth, 2) Midwives’ efforts to minimize the risk of post partum haemorrhage by implementing active management of third stage of labour, 3) Midwives’ perceptions influence attitudes and behaviors in providing care by using risk management approach. Conclusion: Midwives’ perceptions have a pivotal role in attitudes and behaviour during third stage of labour. The application of medical models identified as a result of this perception. Midwives’ need to understand the philosophy of midwifery care to avoid unnecessary medical interventions in all normal childbirth.